High sensitivity detection of cancer in vivo using a dual-controlled activation fluorescent imaging probe based on H-dimer formation and pH activation - Ogawa, Mikako (2010)
The key to improving the sensitivity of in vivo molecular imaging is to increase the target-to-background signal ratio (TBR). Optical imaging has a distinct advantage over other molecular imaging methods in that the fluorescent signal can be activated at the target thus reducing background signal. Previously, we found that H-dimer formation quenches fluorescence of xanthene fluorophores, and among these, TAMRA had the highest quenching ratio. Another approach to lowering background signal is to employ pH activation based on the photon-induced electron transfer (PeT) theory. We hypothesized that combining these two strategies could lead to greater quenching capacity than was possible with either probe alone. A pH-sensitive fluorophore, pHrodo or TAMRA was conjugated to the cancer targeting molecules, avidin (Av) and trastuzumab (Tra). As expected, both pHrodo and TAMRA formed H-dimers when conjugated to avidin or antibody and the dimerization resulted in efficient fluorescence quenching. In addition, pHrodo conjugated probes showed pH-dependent fluorescence activation. When the probes were used in an in vivo animal model, fluorescence endoscopy with Av-pHrodo depicted tumors with high TBR 1 h and 2 h after injection. Av-TAMRA also visualized tumors 1 h and 2 h after the injection, however, TBR was lower due to the background signal from non-specific binding 1 h after the injection as well as background fluorescence from the unbound agent. Thus, we demonstrate that a dual-controlled activatable optical probe based on the combination of H-dimer formation and pH activation can achieve high TBR at early time points during in vivo molecular imaging.